International consensus statement on allergy and rhinology: rhinosinusitis 2021. Issue 3 (14th March 2021) - Orlandi, Richard R.; Kingdom, Todd T.; Smith, Timothy L.; Bleier, Benjamin; DeConde, Adam; Luong, Amber U.; Poetker, David M.; Soler, Zachary; Welch, Kevin C.; Wise, Sarah K.; Adappa, Nithin; Alt, Jeremiah A.; et al.
Abstract : I. Executive Summary: Background: The 5 years since the publication of the first International Consensus Statement on Allergy and Rhinology: Rhinosinusitis (ICAR‐RS) has witnessed foundational progress in our understanding and treatment of rhinologic disease. These advances are reflected within the more than 40 new topics covered within the ICAR‐RS‐2021 as well as updates to the original 140 topics. This executive summary consolidates the evidence‐based findings of the document. Methods: ICAR‐RS presents over 180 topics in the forms of evidence‐based reviews with recommendations (EBRRs), evidence‐based reviews, and literature reviews. The highest grade structured recommendations of the EBRR sections are summarized in this executive summary. Results: ICAR‐RS‐2021 covers 22 topics regarding the medical management of RS, which are grade A/B and are presented in the executive summary. Additionally, 4 topics regarding the surgical management of RS are grade A/B and are presented in the executive summary. Finally, a comprehensive evidence‐based management algorithm is provided. Conclusion: This ICAR‐RS‐2021 executive summary provides a compilation of the evidence‐based recommendations for medical and surgical treatment of the most common forms of RS.